A case study on the changes in clothing choices of a violence against women survivor - Aurelio, Patricia Sybil; Lumawig, Maria Josephine T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
Violence against women (VAW) or domestic abuse, in particular, is a pervasive issue, considered taboo, which victimizes one in every five Filipino women. It is usually long-lasting and bears long-term consequences. Clothing is merited as a signifier of change in a person's life, may it be traumatic in nature or not. This study aimed to analyze changes in clothing choices of a VAW survivor from the pre-abuse, abuse, to the post-abuse phases. Specifically, it looked into changes in garment style, design details, silhouettes, fabrics, and colors of clothing and the motivations of these changes from the lens of the modesty, immodesty, adornment, and protection theories of clothing. Qualitative data for this case study was gathered through personal interviews with a selected VAW survivor and through photo analysis of clothing worn by the respondent. Results showed that the respondent had evident changes in clothing choices in terms of garment style, design details, silhouettes, fabrics, and colors. Clothing choices during the pre-abuse phase included flowy skirts and fitted tank tops in jewel-toned colors. Clothing choices shifted to loose and baggy fit and in neutral colors during the abuse stage. Post-abuse clothing choices reverted to the pre-abuse garment styles but in mostly black-white-grey color scheme. The respondent's clothing was motivated to decorate herself during the pre-abuse phase and for protection during the abuse phase. During the post abuse phase, the clothing changes were motivated by a combination to protect and to display a better version of herself. Recommendations include further studies dealing with more respondents to present a more comprehensive overview of the changes in clothing choices of survivors of Violence Against Women. Validating through further in depth interviews how specific garment styles, design details, silhouettes, fabrics, and colors, as presented in this study, help VAW survivors recover from trauma is also recommended.
Available to the general public.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman
Keywords: Women's clothing -- Philippines; Women -- Crimes against -- Philippines -- Clothing; Clothing and dress -- Social aspects -- Philippines